2013
DOI: 10.1002/ajhb.22491
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding is associated with lower 2D: 4D digit ratio

Abstract: Our results suggest that consanguineous marriages are associated with a fetal environment that influences morphological development and may have associated behavioral sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 59 publications
2
8
1
Order By: Relevance
“…Our present data show that consanguinity of the parents is related to lower and more masculine 2D:4D ratios, confirming the results of our previous study on adults (Özener et al, ). Remarkably, we found that infants of mothers with higher educational level had higher digit ratio.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our present data show that consanguinity of the parents is related to lower and more masculine 2D:4D ratios, confirming the results of our previous study on adults (Özener et al, ). Remarkably, we found that infants of mothers with higher educational level had higher digit ratio.…”
Section: Discussionsupporting
confidence: 93%
“…If digit ratio is indeed a valid indicator of the developmental stability and susceptibility to stress via its relationship with fetal exposure to sex steroids, we can anticipate that inbreeding may affect the digit ratio (a proxy marker of prenatal sex steroid exposure). We have previously shown that (Özener et al, ) across hands and sex, consanguineous parentage is consistently associated with lower, more masculine, digit ratios in Turkish adults. This previous study demonstrates the indirect effects of inbreeding depression on prenatal steroids in adult subjects.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the pattern of reported results is contradictory, that is, a study at a specific locale has reported a positive relationship between family income and 2D:4D ratio (Ozener et al, 2014), whereas an Internet‐based large international study has reported a negative relationship (Manning et al, 2021). Interestingly, Ozener et al (2014) have suggested that the stress, induced by lower socioeconomic status, leads to heightened prenatal testosterone levels and lower digit ratios, whereas Manning et al (2021) have suggested that maternally induced epigenetic response mediates the relationship of family income with lower digit ratios. Thus, because of the prior contradictory findings and explanations, in the present study, we tested the effect of family income on digit ratios without any specific hypothesis.…”
Section: Introductionmentioning
confidence: 99%